Analisis Kemenagan Pasangan Arief R. Wismansyah-Sachrudin Pada Pemilihan Umum Walikota dan Wakil Walikota Tangerang Tahun 2013 - Sidik, Indra Ispriawan; Utomo, Susilo; ., Fitriyah (Journal of Politic and Government Studies, 2014)
General Election of Mayor and Deputy Mayor of Tangerang which took place on August 31, 2013 followed by five pairs of candidates contesting for the seat of Mayor and Vice Mayor. These five pairs of candidates are competing is Harry Mulya Zein-Iskandar, Abdul Syukur-Hilmi Fuad, Dedy Gumelar-Suratno Abu Bakar, Ahmad Marju Kodri-Gatot Suprijanto, and Arief R. Wismansyah-Sachrudin.Number of (DPT) Permanent Voters List Tangerang were 1,161,855 people and the number of valid votes on election day amounted to as much as 726 351. While the number of polling stations (TPS) as many as 2,921 polling stations spread over 104 villages. In the election of 2013 yesterday Tangerang victories achieved by the pair number 5 by a vote as much as 48.01%, followed by pair number 2 by a vote 26.34%, then the pair number 3 by a vote 17.10%, while the pair number 1 and 4 respectively to get the vote by 6.43% and 2.12% .Good cooperation between the winning team, volunteers, and political parties for couples Arief R. Wismansyah-Sachrudin become one of the success factors. Political strategies and political marketing are applied also proved successful and brought the couple occupying the Mayor and Deputy Mayor of the period 2013-2018.Local elections is pentokohan event. In addition to a solid team, and the popularity of the candidate figure greatly affect the success of a candidate in winning the political battle.Keywords : General Election , Political Strategy , Marketing Politics , Tangerang .